Has the COVID-19 Pandemic Affected Community-Acquired Urinary Tract Infections in Children? - Gul , Abdullah; Ekici , Ozgur; Zengin , Salim; Boyaci , Caglar (Urology Journal, 2022)
Purpose: To evaluate whether there were any changes in the rates of urinary tract infection (UTI) and antibiotic resistance in pediatric patients during the pandemic period. Materials and Methods: Urine culture samples collected due to suspected UTI were searched retrospectively from our hospital database, and the patients with growth in urine culture were identified. They were divided into 2 groups as Group A (before COVID-19, March 11, 2019- March 11, 2020) and Group B (COVID-19 period, March 11, 2020- March 11, 2021). Also, COVID-19 period was divided into 3 subgroups (March 2020– June 2020: first epidemic peak, July 2020 – November 2020: normalization process, December 2020– March 2021: second epidemic peak). We adjusted the patient age as <1, 1-6 and 7-18 years. Age, gender, microorganism strain types, and their antibiotic resistance patterns were compared between the 2 groups Results: This cross-sectional study included 250 eligible patients (Group A, n=182 and Group B, n=68) with a mean age of 10.91 ± 5.58 years. The male/female ratio was higher in Group B than in Group A (p = .004). Incidence of UTIs was lower in the curfew and restriction periods due to epidemic peaks than normalization process (p = .001). The proportion of E.coli decreased from 80.2% to 61.8% during the pandemic period when compared to pre-pandemic period (p = .001). Group B had lower rates of resistance to ampicillin, fosfomycin and nitrofurantoin for E.coli than Group A (p = .001, p = .012 and p = .001, respectively). Also, Group B had higher rate of uncommon microorganisms and lower rate of resistance to nitrofurantoin for E.coli than Group A in patients aged 7-18 years (p = .003 and p = .023, respectively). Conclusion: Our study demonstrates that the ongoing COVID-19 pandemic process has caused alterations in community-acquired UTIs in children. More hygienic lifestyle may be considered as the main factor in this change.